2014
DOI: 10.1007/s13277-014-1923-z
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of serum tenascin-c levels in epithelial ovarian cancer

Abstract: Tenascin-C (TNC) is an extracellular matrix protein that is expressed at low levels in normal adult tissue but is highly expressed around many tumors including ovarian tumors. The objective of this study was to determine the clinical significance of the serum levels of TNC in epithelial ovarian cancer (EOC) patients. A total of 50 patients with a pathologically confirmed diagnosis of EOC were included in this study. Serum TNC levels were determined by the solid-phase sandwich enzyme-linked immunosorbent assay … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 17 publications
3
24
0
Order By: Relevance
“…Moreover, a recent study highlighted that serum TNC levels were much higher in patients with epithelial OC than in normal controls. Such high serum TNC levels were related to poorer overall survival, which was consistent with our findings [32].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, a recent study highlighted that serum TNC levels were much higher in patients with epithelial OC than in normal controls. Such high serum TNC levels were related to poorer overall survival, which was consistent with our findings [32].…”
Section: Discussionsupporting
confidence: 92%
“…CAFs have been shown to facilitate cancer progression by supporting tumor cell growth, extracellular matrix remodeling, angiogenesis, and formation of an immunosuppressive microenviroment 71 . These results are supported by our research showing that CAF subtypes CD73_1 and CD73_2 express genes, such as ANGPTL2, TNC, TGFB1, FN1, BMPR1B, and LRRC32, that have been shown to promote tumor progression, angiogenesis, and extracellular matrix remodeling 45,46,52,55,56,75,76 . Some of these genes, including TGFB1, BMPR1B, and LRRC32, have been shown to modulate TGF-β signaling, which suppresses in ltration of anticancer immune cells such as cytotoxic T cells and natural killer cells and promotes the function of pro-cancer immune cells, such as regulatory T cells and M2 macrophages, in the tumor microenvironment 45,77,78 , leading to poor patient survival rates.…”
Section: Discussionsupporting
confidence: 82%
“…Together with increased TGFB1 secreted by CD73_1 and CD73_2 CAFs, LRRC32 may generate an immune-suppressive and pro-tumorigenic microenvironment to support the malignant phenotype of ovarian cancer cells, as we previously described 53,54 . Both FN1 and TNC encode extracellular proteins that have previously been shown to be associated with short progression-free survival and increased migration-inducing potential in HGSC 55,56 .…”
Section: Correlations Between Cell Subtype Density and Transcriptomicmentioning
confidence: 99%
“…8 Moreover, it was shown that serum level of tenascin-C has no predictive or prognostic roles on survival of epithelial ovarian cancer or breast cancer patients. 11,12 These data suggest that tenascin-C expression as cancer marker needs to be considered in a broader context. Tenascin-C was found to be upregulated together with several other ECM molecules in the so called AngioMatrix that is upregulated during the angiogenic switch of an experimental insulinoma model.…”
Section: Exploiting High Tenascin-c Expression In Cancer For Diagnosimentioning
confidence: 99%